TECHNOLOGY OF EDUCATION OF SENSE OF RESPONSIBILITY JUNIOR SCHOOLCHILDREN (Pedagogy of Higher and Secondary Education, 2008)
In the article forming essence opens up among primary pupils of sense of responsibility as facilities, condition and result development, are described modern technologies of development of responsibility.